A arte censurada: teatro e ditadura no Estado da Paraíba nos anos de 1964 a 1988 - Silva, Rosa Maria Carlos e (2014)
The present paper is the result of a bibliographic and documentary research whose main purpose consists in identify how the theater artists of the State Paraiba were struck by theatrical censorship imposed by the military dictatorship during the years 1964-1988, seeking thus contribute with the exercise of the right to memory and truth. Therefore this study deals with the relations of censorship measures with the violation of human rights looking for identify the origin that has given the censorship their policing feature and also underscores the importance to investigate the archives of repression. The text outlines a panorama of censorship legislation set in a timeline that goes from the Vargas dictatorship to the New Republic, illustrating its application with facts and records in the history of Brazilian theater. From the documentation pertaining to the acquis of National Archives that portrays the Paraiba‟s dramaturgy censored, with the use of other sources, the following paper highlights the actions of federal censorship on the work of Paraiba‟s artists, showing that this authoritarian action of military dictatorship reached forcefully Paraíba theater and its artists in the period of utmost lack of liberty of Brazilian people story.